AMPA receptor anchoring at CA1 synapses is determined by N-terminal domain and TARP γ8 interactions - Jake F. Watson (Nature Portfolio, 2021)
Changes in AMPAR localization can control the strength of synaptic transmission. Here, the authors show that the interactions of TARP γ8 and the AMPAR N-terminal domain work together to regulate receptor accumulation and positioning at the post-synapse of mouse hippocampal CA1 neurons.